(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Chromatographic purification and spectroscopic analysis of the constituents from the stem extract of Ipomoea turpethum L. reported 22, 23-dihydro-?-spinasteryl-?-D glucoside (H-1) in addition to salicylic acid and N-p-comaryltyramine. The structures were elucidated by spectroscopic analysis including 1H-NMR and 13C-NMR, 1H-1H COSY, 1H-13C COSY, HMQC, HMBC, UV and IR spectroscopy. 22, 23-dihydro-?-spinasteryl-?-D-glucoside is first reported from Ipomoea turpethum. DOI: http://dx.doi.org/10.3329/jbas.v36i1.10906 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 1, 13-17, 2012